THE EFFECT OF HEALTH EDUCATION WITH AUDIO-VISUAL MEDIA TOWARD EXTERNAL GENITAL HYGIENE BEHAVIORS TO PREGNANT WOMEN IN PRIMARY HEALTH CARE OF MALANG WORKING AREA - Ulfa Fauziyah Hayati; Fransiska Imavike Fevriasanty; Muladefi Choiriyah (Journal of Nursing Science Update (JNSU), 2018)
External genital hygiene is an important part to prevent pregnancy infection. In Indonesia, 75% of genital infection occurance is caused by poor hygiene behaviour. Genital infections causes premature labor, PROM, and neonatal death. Although health education has been given based on visual approaches, 60,9% of pregnant women still have a poor genital hygiene behaviour. The usage of audio-visual media is expectable to improve genital hygiene behaviour of pregnant women. This research is aimed to determine the effect of audio-visual media usagetoward genital hygiene behaviour to pregnant women. Quasy experimental studies using nonrandomizedpretest-posttest control group design and divided into intervention group with audio-visual media and leaflet (n=10) and control group with leaflet (n=10). Samples were selected by accidental-sampling method. Data were collected by questionnaires. The results showed that the increase score of intervention group afterbeing given the education is 4.0(Paired t-Test, p-value=0.000). On the control group, the increase score afterbeing given the education is 1.6(Paired t-Test, p-value=0.005). The result of Unpaired t-Test on the intervention and control group showed that the p-value is 1.000 (p value>0.05). The conclusion is there is not behaviour difference of external genital hygiene on the intervention and control group. The audio-visual media and leaflet usage has a significant effect in improving genital hygiene behavior of pregnant women. It is suggested for researchers to add the usage of education media as aids equipment to measure hygiene behaviour of pregnant women more objective.